1976
DOI: 10.1099/00221287-97-1-63
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation of Purines and their Effect on the Adenylate Energy Charge and Viability of Starved Peptococcus pravotii

Abstract: SUMMARYThe principal products of endogenous metabolism of the obligate anaerobe Peptococcus pre'votii were carbon dioxide, ammonia, acetate and butyrate, which are also produced by fermentation of nucleosides, purines and ribose, thus supporting our previous finding that RNA is the only cellular component to undergo substantial degradation under starvation conditions. Minor products were hydrogen, formate and propionate. The stoicheiometries of fermentation of xanthine, adenine, adenosine and ribose were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1978
1978
1994
1994

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 4 publications
(6 reference statements)
0
10
0
Order By: Relevance
“…We suppose that oxygen consumption by phosphate-deficient cultures is inhibited because the lack of inorganic phosphate prevents conversion of ADP to ATP and, as a consequence, the coupled cytochrome reactions also become inhibited. Phosphate deficiency which impairs the phosphorylation of ADP should result in decreased cell viability (17,21,22,27). Our studies showed that phosphate-limited cells were less viable than phosphate-sufficient cells under identical conditions (Fig.…”
Section: Encystment Studies Cultures Of a Vinelandiimentioning
confidence: 64%
See 1 more Smart Citation
“…We suppose that oxygen consumption by phosphate-deficient cultures is inhibited because the lack of inorganic phosphate prevents conversion of ADP to ATP and, as a consequence, the coupled cytochrome reactions also become inhibited. Phosphate deficiency which impairs the phosphorylation of ADP should result in decreased cell viability (17,21,22,27). Our studies showed that phosphate-limited cells were less viable than phosphate-sufficient cells under identical conditions (Fig.…”
Section: Encystment Studies Cultures Of a Vinelandiimentioning
confidence: 64%
“…5). This was expected since cells with a low adenylate energy charge are considered to be less likely to survive even very gentle stress than those with a higher adenylate charge (17,21,27). Since these cells were suspended in saline solution (0.85% NaCl) in the absence of oxidizable substrate, death probably resulted from depletion of ATP and inability to generate sufficient energy (ATP) to maintain life (5,6).…”
Section: Encystment Studies Cultures Of a Vinelandiimentioning
confidence: 99%
“…The oligotrophic and copiotrophic marine bacteria are examples of organisms with extreme longevity (1,25). On the contrary, the facultative and obligate anaerobic chemoheterotrophs studied thus far, i.e., Streptococcus lactis (36), S. faecalis, and other Streptococcus species (31), Staphylococcus epidermidis (11), Peptococcus prevotii (30), Ruminococcus flavefaciens (45), and Selenomonas ruminantium (22,23) are more sensitive to nutrient starvation and lose their viability within a few days.…”
mentioning
confidence: 99%
“…Adenine is the only naturally occurring purine which is not attacked by these species (6,9). Under anaerobic conditions, the degradation of adenine has been reported for "Peptococcus aerogenes" (56), Peptococcus prevotii (36), and Clostridium sticklandii (37). Veillonella alcalescens deaminates adenine to some degree (57).…”
Section: Institut Fur Mikrobiologie Der Uniuersitat Gottingen Federmentioning
confidence: 99%